Pengaruh Financial Literacy Terhadap Sustainability UMKM Di Kota Padang - Tesi Wulandari; Ratnawati Raflis (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
This study analyzes the influence of Financial Literacy on the Sustainability of MSMEs in Padang City. Financial literacy is measured through knowledge, behavior, and attitude indicators, while sustainability is assessed through financial growth, strategic, structural, and organizational dimensions. Using a quantitative approach, a survey was conducted with 379 MSME owners across five districts. Data analysis was performed using Structural Equation Modeling–Partial Least Square (SEM-PLS) via SmartPLS. The results indicate that Financial Literacy has a positive and significant effect on Sustainability, with a coefficient of 0.527, a t-value of 14.215 (>1.96), and a p-value of 0.000 (<0.05). The R-Square value of 0.278 suggests that financial literacy explains 27.8% of the variation in sustainability, while other factors account for the remainder. These findings confirm that higher financial literacy among MSME owners leads to greater business sustainability, enabling them to navigate economic challenges more effectively.